2017
DOI: 10.1016/j.scitotenv.2017.03.146
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a crop model and a geochemical model as a new approach to evaluate the sustainability of an intensive agriculture system

Abstract: By combining a crop model (STICS) and a geochemical model (PHREEQC), a new approach to assess the sustainability of agrosystems is proposed. It is based upon aqueous geochemistry and the stepwise modifications of soil solution during its transfer from the surface till aquifer. Meadows of Crau (SE France), irrigated since the 16th century, were field monitored (2012-2015) and modelled. Except for N, the mineral requirements of hay are largely covered by dissolved elements brought by irrigation water with only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Besides, several new techniques and application have been introduced and patented to improve the traditional agriculture practices. However, experts mainly focused and monitor the climatic condition, soil properties, water quality, plant development, livestock management, and fertilizer application, pesticide application, and illumination control through various intelligent techniques [26][27][28][29][30][31][32]. Meanwhile, it could be concluded that traditional agricultural logistics is improved and upgraded by introducing and implementing the several modern technologies and techniques in agriculture domains [33].…”
Section: Related Workmentioning
confidence: 99%
“…Besides, several new techniques and application have been introduced and patented to improve the traditional agriculture practices. However, experts mainly focused and monitor the climatic condition, soil properties, water quality, plant development, livestock management, and fertilizer application, pesticide application, and illumination control through various intelligent techniques [26][27][28][29][30][31][32]. Meanwhile, it could be concluded that traditional agricultural logistics is improved and upgraded by introducing and implementing the several modern technologies and techniques in agriculture domains [33].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers especially focus on the domains of monitoring, control, logistics and prediction. Monitoring objectives include air condition [ 20 ], soil [ 21 ], water [ 22 ], plant [ 23 ] and livestock [ 24 ]. Control objectives include fertilizer and pesticide [ 25 ], illumination [ 26 ] and access [ 27 ].…”
Section: Introductionmentioning
confidence: 99%